Assessment of knowledge of multipurpose health workers regarding adverse events following immunization in a rural block of Haryana, India - Gupta, Nishu C.; Rathod, Kamleshkumar G.; Garg, Lalita R. (International Journal of Contemporary Pediatrics, 2019)
Background: No vaccine is entirely free from the risk of adverse reactions or remote sequel. Knowledge and reporting of AEFI is very important in this vaccine era. Objective of the study was to assess the knowledge of Multipurpose Health Workers (MPHWS) regarding AEFI. Methods: A cross-sectional study was undertaken on randomly selected 30 MPHWs of Beri block. A semi-structured questionnaire was administered after taking verbal consent. The MPHWs had a minimum of one year experience and had received the latest formal training during measles catch up campaign. Data compiled and analysed using appropriate statistical tests. Results: A total of 30 MPHWs duly completed and returned their questionnaires. The mean age was 36.5±2.54 years and mean post-qualification experience was 5.3 years. About 83% of the MPHWs knew that fever, pain, redness and swelling at injection site were symptoms of AEFI and 93% knew about proper storage temperature, dose, route and site of vaccines. Only 56% knew about the storage temperature of diluents and risk of its contamination, 30% knew proper reconstitution of the vaccine. Only 33% knew about filling an adverse event form to report an AEFI. Twenty-five (83.5%) MPHWs had encountered an AEFI and only 14(46.6%) reported such within 24 h. It was observed that level of correct knowledge was decreasing with increasing age of respondents. Conclusions: There was a lack of knowledge about the cause, identification and reporting of AEFI despite periodic training programmes. There is need to train the health workers to improve reporting and prevent complications due to vaccines. There is also further need to ponder over the lacunae in training programmes responsible for persistent inadequate knowledge among MPHWs. Last but not the least “DO NOT FURTHER HARM” should always be the primary aim.